Bridging a digital divide: A critical analysis of contextual factors affecting ICT integration in Philippine schools - Espinosa, Allen A; Ma. Arsenia C. Gomez; Miranda, Praksis A; David, Adonis P; Edna Luz R. Abulon; Ma. Victoria C. Hermosisima; Quinosa, Edwin A; Soliman, Abegail A; de Vera, Jayson L; Claros, Ian Harvey A; Hardie Gieben M. Cruz; Gonzales, Nepthalie SJ (Issues in educational research, 2025)
Our study provides a critical exploration of the factors limiting equal access to educational technology (EdTech) in the Philippines. Despite the Department of Education's commitment to using technology to improve learning outcomes, the Covid-19 pandemic has deepened existing disparities. Utilising a combination of a systematic literature review and qualitative data from interviews and focus group discussions, our research identifies key requirements for successful EdTech implementation. The study underscores the need for infrastructure development, leadership support, and strong partnerships to address these gaps. It offers strategic recommendations aimed at enhancing access to digital learning and supporting the nation's educational reform initiatives.